Optimalisasi Peran Kepala Sekolah dalam Meningkatkan Motivasi Kerja Guru Melalui Pemberian Tugas Tambahan - H. Soro, Suharyanto; Wijayanti, Azizah Huda; Ridawati, Ridawati; Nelda, Elfita (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The role of the school principal in increasing teacher motivation, teaching quality, student achievement, and school performance is highly necessary in every educational institution. That is why, the school principal is demanded to have competences to get the objective of the school. Giving the task and opportunity to develop teacher competence by the school principal is not appropriate and still far from the fact. This research aims (1) To explain the principal's role in increasing teacher activities, thus motivating and fostering a work ethic among teachers that impacts the quality of educational institutions in the region; (2) To assign additional tasks, supporting teachers in attending up-to-date training outside of school, and organizing activities related to quality improvement are strategies employed by the school principal. The researchers used qualitative research method. The data was collected through observation, interview, and documentation methods. The respondents in this research chosen by purposive sampling. They are school principal and teachers. The research was conducted at Elementary School Negeri 14 Petang, Rawalele, Kalideres, West Jakarta academic year 2024. The data was processed through data reduction, data presentation, and conclusion drawing. The reseach finding indicated that (1) the principal of SDN Kalideres 14 Petang has carried out his role optimally in order to increase teacher motivation and work ethic. In this context, school principals implement various strategies based on the needs and conditions faced by the educational unit; (2) School principals always carry out evaluations in order to ensure that learning activities packaged in the form of additional assignments can increase teacher work motivation and professionalism.